2007
DOI: 10.1152/ajpheart.01057.2006
|View full text |Cite
|
Sign up to set email alerts
|

Age alters cerebrovascular inflammation and effects of estrogen

Abstract: In young adult females, estrogen treatment suppresses the cerebrovascular inflammatory response; this is mediated in part via NF-kappaB, a key regulator of inflammatory genes. To examine whether age modifies effects of estrogen on vascular inflammation in the brain, female rats, 3 and 12 mo of age, were ovariectomized; half were treated with estrogen for 4 wk. Cerebral blood vessels were isolated from the animals at 4 and 13 mo of age. Inflammation was induced by LPS, either injected in vivo or incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 55 publications
1
30
0
1
Order By: Relevance
“…In WT and NKLAM-KO macrophages stimulated with LPS, p65 expression levels increased over time. Similar LPS-stimulated p65 expression kinetics has been observed in other experimental systems (Sunday, et al, 2007). The p65 expression kinetics is nearly identical in WT and NKLAM-KO BMDM; however, total p65 expression was lower in NKLAM-KO than in WT macrophages (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…In WT and NKLAM-KO macrophages stimulated with LPS, p65 expression levels increased over time. Similar LPS-stimulated p65 expression kinetics has been observed in other experimental systems (Sunday, et al, 2007). The p65 expression kinetics is nearly identical in WT and NKLAM-KO BMDM; however, total p65 expression was lower in NKLAM-KO than in WT macrophages (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Sunday et al [25] showed that the protective, anti-inflammatory effect of estrogen on cerebral blood vessels in young adult rats was attenuated in aged animals; the ratio of nuclear to cytoplasmic levels of nuclear factor kappa B (NF-kB), a key regulator of inflammatory genes, was higher in aged than young rats. Sherwood et al [26] suggested that the benefit of natural estrogen supplementation on vascular endothelial function may be dependent on the postmenopausal age and that improved vascular function is elicited only in the early postmenopausal years.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in rats estrogen has been shown to suppress vascular inflammatory responses to IL-1␤ and lipopolysaccharide treatments, and this response has also been shown to vary through the estrous cycle (Galea et al, 2002;Ospina et al, 2004;Sunday et al, 2006). An intriguing result is that this anti-inflammatory effect of estrogen is lost in older female animals (Miller et al, 2004a;Sunday et al, 2007).…”
Section: A Inflammationmentioning
confidence: 99%